123 Distinct Molecular Mutations in Synchronous Lung Cancers. (11th January 2018) - Wang, Kai; Marbut, Stephen; Harada, Shuko; Guo, Rongjun
Abstract: Incidence of synchronous lung carcinomas is rare. Making a definitive diagnosis of synchronous lung carcinomas is in many cases difficult by conventional morphological pathology. Molecular analysis may be very helpful in this regard as well as for targeted therapy. Here, we present three cases with synchronous double lung cancers proved by molecular analysis. The first case was a 68-year-old woman with two separate lung masses, one in the left upper lobe and the other in the right lower lobe. The histological features of these two tumors were almost indistinguishable. KRAS mutation analysis was performed and identified a c.35G>T, p.G12V mutation in the tumor of the left upper lobe and a distinct c.35G>A, p.G12D mutation in the tumor of the left lower lobe. The second case was a 78-year-old woman. Two lung nodules were resected, both from the left lower lobe. Histologically, both were well differentiated adenocarcinoma. Molecular studies identified a missense mutation, p.L858R of the EGFR gene, in the first nodule, and two missense mutations, p.L861Q (exon 21) and p.G719A (exon 18) of the EGFR gene, in the second nodule. The third case was an 80-year-old woman with two lung nodules. They were resected separately in an interval of five months. Histologically, both tumors were adenocarcinoma with lepidic features. Molecular analysis identified a KRAS p.G12V in one nodule, but no mutations were identified in the other tumor. Without these molecular findings, it would have been difficult, if not possible, to determine whether these tumors were two independent primaries or one tumor was the metastasis from the other tumor. Thus these findings suggested that molecular analysis may be a powerful approach to demonstrating tumors' independence. Potentially, molecular analysis can also be utilized as a biomarker to track the tumors when they become recurrent or metastatic.